Pulmonary hypertension in the premature infant: a challenging comorbidity in a vulnerable population. Issue 3 (June 2016) - O'Connor, Michael Glenn; Cornfield, David N.; Austin, Eric D.
Abstract : Purpose of review: This review is written from the perspective of the pediatric clinician involved in the care of premature infants at risk for pulmonary hypertension. The main objective is to better inform the clinician in the diagnosis and treatment of pulmonary hypertension in premature infants by reviewing the available relevant literature and focusing on the areas for which there is the greatest need for continued research. Recent findings: Continued knowledge regarding the epidemiology of pulmonary hypertension in the premature infant population has aided better diagnostic screening algorithms. Included in this knowledge, is the association of pulmonary hypertension in infants with bronchopulmonary dysplasia (BPD). However, it is also known that beyond BPD, low birth weight and other conditions that result in increased systemic inflammation are associated with pulmonary hypertension. This information has led to the recent recommendation that all infants with BPD should have an echocardiogram to evaluate for evidence of pulmonary hypertension prior to discharge from the neonatal ICU. Summary: Pulmonary hypertension can be a significant comorbidity for premature infants. This review aims to focus the clinician on the available literature to improve recognition of the condition to allow for more timely interventions.